Out-of-Hospital Intubation and Bronchoscopy Using a New Disposable Device: The Initial Case. (1st November 2020) - Yamauchi, Sunao; Tagore, Ammundeep; Ariyaprakai, Navin; Geranio, Josephine V.; Merlin, Mark A.
Abstract: Airway management is one of the critically important skills in practicing emergency medicine. However, intubation in the prehospital setting is quite different from those done in controlled environment and still poses significant risks for serious complications. Although checking for clinical findings and end-tidal carbon dioxide detection system (ETCO2) are well-established and widely adopted way to verify ETT placement in the prehospital setting, there are certain situations that the use of these methods could be unreliable. The use of advanced flexible bronchoscopy technology allows us to directly visualize the tube placement and can also assist difficult intubation. Studies have shown that the verification of tube placement utilizing bronchoscopy is an easy and highly reliable methods and this is especially beneficial in the prehospital settings. Although the use of bronchoscopy in prehospital setting currently is somehow limited, this new, rapidly advancing technology and technique is believed to be a game changer in our prehospital intubation/post-intubation practice in the near future.